Fosfomycin Susceptibility Among Urinary Isolates of Escherichia Coli at a Tertiary Care Teaching Hospital (GAIMS Journal of Medical Sciences, 2024)
Background: Urinary Tract Infection (UTI) is a prevalent infectious disease caused by Enterobacteriaceae, with Escherichia coli being the predominant etiological agent. The rise in multidrug resistance (MDR) and dearth of effective oral antibiotics have constrained the therapeutic option for UTIs. Fosfomycin, an orally administrated bactericidal broad-spectrum antibiotic exhibits activity against MDR pathogens. The aim of this study was to assess in vitro efficacy of Fosfomycin against Escherichia coli isolates.Materials and Methods: This descriptive cross-sectional study spanned a duration of 6 months. A total of 3782 samples were collected from suspected UTI patients and processed. Escherichia coli isolates were identified by conventional method and subjected to in vitro susceptibility testing to Fosfomycin and other commonly utilized antibiotics by Modified Kirby-Bauer disk diffusion method.Results: Among 3782 samples, 929 (24.56%) exhibited significant colony growth, with Escherichia coli accounting for 378 (40.6%) of the positive isolates. Higher rates of resistance were observed for Nalidixic acid (92.60%), Norfloxacin (78.58%) and Doxycycline (76.99%). Of the Escherichia coli isolates, 269 (71.76%) isolates were identified as MDR isolates. The susceptibility of Escherichia coli isolates to Fosfomycin was 95.23%, while that of MDR Escherichia coli isolates was 95.54%.ConclusionFosfomycin exhibits excellent in vitro susceptibility against MDR Escherichia coli isolates in UTIs, suggesting its potential as a promising alternative oral agent for outpatient therapy of UTI.